Strategic Action Programme for the Red Sea and Gulf of Aden : Country Reports - Regional Organization for the Conservation of the Environment of the Red Sea and Gulf of Aden (Washington, DC: World Bank, 2013)
The Red Sea and Gulf of Aden contain some of the world's most important coastal and marine environments and resources. In view of their environmental uniqueness, the threats they are facing, and the need for actions, the preparation of the Strategic Action Programme (SAP) for the Red Sea and the Gulf of Aden was initiated in October 1995. THE SAP process, coordinated by the Regional Organization for the Conservation of the Environment of the Red Sea and Gulf of Aden (PERSGA), has been undertaken with support from the countries of the region, the Global Environmental Facility (GEF), selected international development institutions, and donor organizations. The SAP supports and facilitates the primary goal of PERSGA, which is the conservation of the environment of the Red Sea and Gulf of Aden. The goals of the SAP are to develop a regional framework for protecting the environment and the sustainable development of coastal and marine resources. The Program outlined in the SAP focuses on both preventive and curative measures required to maintain the rich and diverse coastal and marine resources of the Red Sea and Gulf of Aden. The SAP is a significant process for reaching agreement concerning environmental trends, threats, and priorities at a regional level. It is also a product in the form of an Action Programme which provides a framework for continued cooperation in reaching short-, medium-, and long-term goals through a series of complementary actions at all levels.